Life Cycle Impact Assessment (LCIA), A Decision Making Approach in Waste Water Treatment Plant: A Case Study (International Journal of Built Environment and Sustainability, 2024)
Environmental foot print of a waste water treatment plant is an important criterion to assess the performance of treatment unit. The novel waste water treatment technology was used to clean waste water up to a certain limit. Therefore, in whole process, beginning from electricity production to final disposal of water these treatment technologies can affect our environment. This environmental foot print can be determined by using CML 2000 guideline.  In final performance of a waste water treatment plant environmental ill effects should also be incorporated instead of only using treatment efficiency, CML 2000 gives environmental   performance. In this study four waste water treatment technologies namely Activated Sludge Process, up flow Anaerobic Sludge Blanket, Membrane Biofilm Bioreactor, Fluidized Aerobic Bed were taken. The environmental performance of all these novel technologies was assessed on the basis of eutrophication, global warming potential and removal efficiency, characterization factors are normalized by using CML 2000 guideline. The maximum and minimum results of Acidification was obtained as 0.2215 & 0.0569 in UASB and FAB respectively. The maximum and minimum results of Eutrophication was attained as 0.564 & 0.055 in MBBR and ASP respectively.
Keywords: Life cycle assessment; Activated Sludge Process; Membrane Biofilm Bioreactor; up flow Anaerobic Sludge Blanket; Acidification